Targeting of p53-transcriptional dysfunction by conditionally replicating adenovirus is not limited by p53-homologues - Kühnel, Florian; Gürlevik, Engin; Wirth, Thomas C.; Strüver, Nina; Malek, Nisar Peter; Müller-Schilling, Martina; Manns, Michael P.; Carnero, Amancio; Zender, Lars; Kubicka, Stefan (Molecular therapy, 2010)
A hallmark of human tumors is the loss of p53 or its transcriptional functions. In this study, we describe the generation of the conditionally replicating adenovirus Adp53sensor for the treatment of p53-dysfunctional tumors. p53-selective attenuation of viral replication was achieved by using p53-dependent expression of the transcriptional repressor Gal4-KRAB that was directed against the adenoviral E1A locus. Adp53sensor shows efficient replication in p53-dysfunctional, but not in p53-active cells. In p53-dysfunctional cells, p53-analogous transcriptional activity by other p53 family members was not sufficient to compromise replication of Adp53sensor. In comparison with a genetically similar, but p53-insensitive virus, Adp53sensor replication was inhibited after systemic infection of p53-wt-mice, but not in p53-ko-mice thus confirming the correct function of the chosen approach. Adp53sensor showed efficient lytic and replicative properties in all investigated cells with p53-dysfunction and successfully inhibited the growth of subcutaneous xenotransplants in vivo. We further demonstrated that intravenous injection of Adp53sensor lead to significantly reduced liver damage compared to the control virus. Together, our data show that Adp53sensor is an oncolytic, p53-selective adenovirus for efficient treatment of p53-dysfunctional tumors with a favorable toxicity profile. Moreover, Adp53sensor provides a strategy that should be applicable to other transcriptionally regulated DNA viruses.
Elektronische Reproduktion der Druckausgabe
Gesehen am 07.03.2023